A Need Analysis of Forensic Linguistics Teaching Material Development For University - Sabriandi Erdian; Hasnidar Hasnidar; Ely Ezir; Ernawati Br Surbakti (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2019)
Realizing the university's vision and mission requires teaching materials for the development of education and teaching. The development of forensic linguistic teaching materials is an application that is used to achieve goals, objectives, intention in dealing with various criminal cases that occur in the community. The aim of developing forensic linguistic teaching materials in higher education is an academic need in the current era.. It is a Research and Development Research. It is found that many students are interested to study about forensic linguistics. It is also supported by the lecturers who think that by teaching this lesson in the university will develop their knowledge and skill in linguistics